(untitled) (The National University Journal of Humanities, Social Sciences and Business Studies, 2023)
The main objective of this study is to investigate women empowerment in nongovernmental organizations’ profile in Bangladesh. It discusses the scope of the women empowerment concept of the four big nongovernmental organizations in Bangladesh such as Grameen Bank, Bangladesh Rural Advancement Committee, Proshika and Association for Social Advancement. This paper is based on the literature and studies that highlight the women empowerment issue of these four NGOs. Results showed that two NGOs such as Bangladesh Rural Advancement Committee and Proshika consider their women empowerment issue comparatively from a broader view that includes a number of programmes. On the other hand, the rest of the two nongovernmental organizations initiated the women empowerment activities comparatively from a narrower perspective. The overall findings indicate that the concept of women empowerment in all four nongovernmental organizations is concerned as a global concept where contextual perspective in of women empowerment is less considered. In this connection, this paper argues that due to the low level of focus on the contextual perspective, the contribution of nongovernmental organizations to the women empowerment in Bangladesh is not up to the mark in consideration to the duration they are working towards women empowerment. The findings of the paper would be an important guideline to the policy makers, managers of nongovernmental organizations and development practitioners. NU Journal of Humanities, Social Sciences & Business Studies Vol. 7 & 8, No.2 & 1, July 2021 - December 2022 p. 111-126